The efficiency and safety of multidetector computed tomography‐guided transseptal puncture during atrial fibrillation catheter ablation - Yi Lu; Zhen Yuan; Chunhui Liu; Shenghui Ma; Li Shu; Zhejun Cai (Journal of Arrhythmia)
Abstract Background Transseptal puncture (TSP) is a crucial technique for catheter ablation of atrial fibrillation (AF). Although intracardiac echo (ICE) facilitates a safe and accurate TSP, it is not widely used in developing countries because of the expense. This study evaluated the efficiency and safety of a novel cardiac multidetector computed tomography (MDCT)‐guided TSP during AF catheter ablation. Methods The study consisted of two cohorts. In the index cohort, TSP procedure was performed under the guidance of ICE, and we recorded the angulation of right anterior oblique of X‐ray projection. In the validation cohort, we compared the efficiency and safety of TSP guided by MDCT‐calculated angulation with propensity‐score‐matched patients who underwent TSP guided by ICE. Results We included 50 patients in the index cohort, and the mean angles of interatrial septum (IAS) measured from MDCT and ICE were 34.8 ± 6.3 and 35.1 ± 6.5, respectively. In the validation cohort, 376 patients were enrolled in the MDCT‐guided group and ICE‐guided group. Both groups had 1 case of cardiac tamponade. The mean axial plane angle was 35.46 ± 6.17 degrees, which was not influenced by age, gender, BMI, and LA size, while a moderate positive linear correlation between EF and the axial plane angle (R2 = 0.14, p = .006). Conclusion Cardiac MDCT can provide a clear vision of IAS orientation, and provide the appropriate RAO angle and height for TSP. The efficiency and safety of our MDCT‐guided TSP were comparable to ICE‐guided TSP, which may serve as an alternative method for TSP with ICE unavailable.